Aqueous Supercapacitor with Ultrahigh Voltage Window Beyond 2.0 Volt. Issue 1 (9th September 2020) - Liu, Ji-Chi; Huang, Zi-Hang; Ma, Tian-Yi
Abstract : Supercapacitors (SCs), a new type of green electrochemical energy storage device with high power density and long‐term durability, show great potential to replace nonrenewable energy sources. Benefiting from both economic and environmental advantages, aqueous SCs represent a fabulous prospect in many industries. However, the relative low voltage window of aqueous SCs hinders their further development. In the recent years, especially within the last five years, the significant achievements in aqueous SCs with ultrahigh voltage window (>2.0 V) have been reported. Herein, the effects of theoretical mechanisms on voltage window are first introduced, which provide the fundamental guidance to enlarge the voltage window of aqueous SCs. Subsequently, the strategies for constructing the aqueous SCs over 2.0 V are comprehensively summarized and classified into the electrode modification by structural engineering, metal cations doping and constructing advanced composites, and the electrolyte optimization by preparing "Water in Salt" and novel mixed electrolyte. Finally, via the discussion of current progresses and drawbacks of these >2.0 V aqueous SCs, their future development directions are proposed. Abstract : Aqueous supercapacitor with the strategies that push voltage window breaking the bottleneck of 2.0 V becomes an emerging hotspot. Herein, these strategies are thoroughly summarized and systematically classified into five categories based on various methods of electrode modification and electrolyte optimization. Meanwhile, the corresponding theoretical mechanisms are specially discussed.